Lithotripsy by Holmium Laser (Endoscope) in the Major Operating Room of Al-Sadr Hospital / Najaf - Alhussien, Khadija Hamed Abd; Muhammad, Mustafa Tarrad Obaid; Ahmed, Ali Shaker Mahmoud; Kzar Mokhef, Najlaa Mohammed; Abdul Zaid Karim, Mohammed Baqer Osama (Innovative: International Multidisciplinary Journal of Applied Technology (2995-486X), 2024)
laser is a device that projects a highly concentrated narrow beam of light which is amplified using stimulated radiation. Lasers have three properties: coherency, collimation and monochromatic properties. These three properties of lasers produce a small focus point of intense power. This paper is a basic introduction to laser physics, especially that relevant to accelerator science. It presents the essential physics of a laser, some of the different types of laser system available, the propagation of laser beams, and the key diagnostics that are used for lasers.laser, a device that stimulates atoms or molecules to emit light at particular wavelengths and amplifies that light, typically producing a very narrow beam of radiation. The emission generally covers an extremely limited range of visible, infrared, or ultraviolet wavelengths. Many different types of lasers have been developed, with highly varied characteristics. Laser is an acronym for “light amplification by the stimulated emission of radiation. "In the following papers, the types, characteristics and uses of lasers will be explained with the difference between light and laser with photos and research samples.